Analisis Kepastian Hukum Jaminan Sosial Ketenagakerjaan Bagi Gig Worker Pada Era Gig Economy Di Indonesia - Stevania, Maudy; Hoesin, Siti Hajati (Jurnal Ilmiah Penegakan Hukum, 2024)
This research aims to analyze the legal relations and the legal certainty of social security for gig workers. The issue focuses on the uncertainty of the legal relations and the protection of workers social security for gig workers. Indonesia does not have regulations that govern protection for gig workers, while the growth of gig workers in Indonesia is very rapid. Many companies that provide platform for gig workers to work classify gig workers as partners not as an employee. This partnership results in gig workers not receiving the same protection as a regular worker. Data were collected through doctrinal methods and analyzed qualitatively. This study concludes that the legal relationship between gig workers and companies is often categorized as a partnership relationship. Therefore, to provide legal certainty of employment social security for gig workers, the government need to review the current regulations or create specific regulations to determine work relationships between gig workers and the company that hired them, creating specific regulations for gig workers, also giving a socialization and education for gig workers about the importance of social security to increase their awareness.